Design of 2x2 MIMO Microstrip Antenna With 4 Circular Patch Array Elements for Wifi Technology at 2.4 GHz Operating Frequency - Damanik, Aufar Martanggi; Kusumawardhani, Eka; Imansyah, Fitri (Faculty of Engineering, Universitas Tanjungpura, 2024)
2x2 MIMO antenna design with 4 circular patch array elements for WiFi Technology using CST Studio Suite 2019 software to get an antenna that can work at the 2.4 GHz frequency. This antenna has a circular patch shape with a proximity coupled supply method and uses a 2x2 MIMO system with multilevel impedance arranged with an array supply. The material used to design this antenna is FR-4 Epoxy substrate with a dielectric constant (Îµr) of 4.3 with a thickness (h) of 1.6 mm. An analysis will be carried out on the antenna starting from single patch to MIMO 2x2 on 4 patches on each antenna. The design results of the 2x2 MIMO antenna have obtained return loss values of -21,874 dB and -21,888 for ports 1 and 2, VSWR values of 1,175 and 1,174, gain obtained the same value of 3,661 dBi, with a bandwidth value of 112.5 MHz and a radiation pattern The result is omnidirectional. The antenna design has a patch radius of 27.66 mm with total antenna dimensions of 680x140x3.235 mm3. The design results are in accordance with the initial specifications, so that a 2x2 patch circular MIMO antenna can be realized at the 2.4 GHz frequency.